Development of Project-Based Learning E-Module Integrated with Local Wisdom of Kupang Sidoarjo to Improve Students Creative Thinking Skills - Asnani; Fida Rachmadiarti; Rinie Pratiwi (Yayasan Darussalam Bengkulu, 2026)
This study aimed to develop and evaluate a Project-Based Learning (PjBL) e-module integrating the local wisdom of Kupang Sidoarjo to support Grade X students’ creative thinking in biodiversity learning. The study employed a Research and Development approach using the 4D model—Define, Design, Develop, and Disseminate—and a one-group pretest–posttest design at MAN Sidoarjo, East Java. Participants included two biology teachers and 36 students in the needs assessment, three expert validators, and 70 students in classroom implementation. Data were collected through interviews, questionnaires, validation and readability sheets, implementation observations, student responses, and four essay items assessing fluency, flexibility, originality, and elaboration. Data were analysed using descriptive statistics, the Fry Readability Formula, the Shapiro–Wilk test, the Wilcoxon Signed-Rank Test, effect size, and normalized gain. The e-module obtained a mean validation score of 3.56, indicating very high validity; its average readability corresponded to Grade 11, while classroom usability remained appropriate for Grade X students. Implementation fidelity reached 3.73, and all student-response dimensions exceeded 90%. Creative-thinking scores increased from 49.29 to 88.53, with a high N-gain of 0.76 and a significant pretest–posttest difference (Z = −7.213, p < .001, r = .86). These findings indicate that contextual PjBL activities grounded in documented local wisdom can facilitate authentic problem-solving and creative engagement, consistent with previous research on project-based and contextual learning. However, the single-school, one-group design and single-rater scoring limit causal inference and generalizability; future studies should employ controlled multisite designs, larger samples, and multiple raters.